Multilevel Conductance Switching of a Memory Device Induced by Enhanced Intermolecular Charge Transfer - Gu, Qian-Feng; He, Jing-Hui; Chen, Dong-Yun; Dong, Hui-Long; Li, You-Yong; Li, Hua; Xu, Qing-Feng; Lu, Jian-Mei (Advanced materials (Weinheim), 2015)
The modification of the terminal electron‐donating groups induces a critical change in molecular aggregation and the intermolecular charge‐transfer effect of the symmetric D–A1–A2–A1–D molecules that correlate with an addressable variation of memory performance from binary to ternary.